Penerapan ISAK 35 Pada Penyajian Laporan Keuangan di SMP IT Abu Bakar Yogyakarta - Suyanti Suyanti; Maria Entina Puspita (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to find out how the presentation of financial reports at the Abu Bakar Yogyakarta Integrated Islamic Junior High School aligns with ISAK 35. The financial reports of schools under foundations are regulated in ISAK No. 35 concerning the Presentation of Non-Profit Oriented Financial Reports replaces PSAK No. 45 which became effective on January 1 2020. The method in this research uses qualitative methods based on a descriptive analysis approach. The subject chosen in this research was the Abu Bakar Yogyakarta Integrated Islamic Junior High School with financial reports being the research object. The technique used in collecting information was carried out by means of direct observation and interviews with the school financial manager, namely the school treasurer, to obtain substantial information. The results of the research conducted show that the financial reports presented by school treasurers do not include all the financial reports of non-profit oriented entities contained in ISAK No. 35.